2023
DOI: 10.1556/2006.2023.00014
|View full text |Cite
|
Sign up to set email alerts
|

Reduced loss aversion in value-based decision-making and edge-centric functional connectivity in patients with internet gaming disorder

Abstract: Background and aimsImpaired value-based decision-making is a feature of substance and behavioral addictions. Loss aversion is a core of value-based decision-making and its alteration plays an important role in addiction. However, few studies explored it in internet gaming disorder patients (IGD).MethodsIn this study, IGD patients (PIGD) and healthy controls (Con-PIGD) performed the Iowa gambling task (IGT), under functional magnetic resonance imaging (fMRI). We investigated group differences in loss aversion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Delay discounting tasks have shown that individuals with IGD are more likely to prioritize immediate rewards (Weinsztok, Brassard, Balodis, Martin, & Amlung, 2021). Additionally, imbalanced cost-benefit weighting, where the expected effect of risky behaviors outweighs the potential negative consequences, contributes to a higher propensity for harmful risk-taking behaviors in individuals with IGD (Hong, Liang, Pan, Jin, Luo, Li et al, 2023). While individuals with IGD and HCs may demonstrate similar risk propensities when risky behaviors are favorable, individuals with IGD exhibit significantly higher risk propensities when faced with unfavorable outcomes (Y.…”
Section: Discussionmentioning
confidence: 99%
“…Delay discounting tasks have shown that individuals with IGD are more likely to prioritize immediate rewards (Weinsztok, Brassard, Balodis, Martin, & Amlung, 2021). Additionally, imbalanced cost-benefit weighting, where the expected effect of risky behaviors outweighs the potential negative consequences, contributes to a higher propensity for harmful risk-taking behaviors in individuals with IGD (Hong, Liang, Pan, Jin, Luo, Li et al, 2023). While individuals with IGD and HCs may demonstrate similar risk propensities when risky behaviors are favorable, individuals with IGD exhibit significantly higher risk propensities when faced with unfavorable outcomes (Y.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a longitudinal study of ReHo markers during natural recovery from IGD highlighted the critical involvement of specific brain regions including the dorsolateral prefrontal cortex (DLPFC), orbitofrontal cortex (OFC), and superior frontal gyrus (SFG), which are linked to reward and inhibitory control processes ( 16 ). Current research on FC has thoroughly explored the impact of IGD on dopamine reward system processing ( 17 , 18 ), decision-making cognition ( 19 ), self-control ( 20 ), and attentional bias ( 21 ). Brain regions implicated in the pathophysiology of IGD often reflect deficits in self-monitoring, attention, interoception, motor control, and auditory processing, with its development and maintenance involving complex networks such as the default mode network (DMN), executive control network, and salience network ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%